2019
DOI: 10.1111/flan.12390
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in L2 achievement mirror individual differences in L1 skills and L2 aptitude: Crosslinguistic transfer of L1 to L2 skills

Abstract: Studies with U.S. secondary second language (L2) learners have revealed individual differences (IDs) in first language (L1) skills and L2 aptitude and shown that these IDs are related to L2 achievement and proficiency. In this study, U.S. students were administered measures of L1 achievement, L1 cognitive processing, and L2 aptitude; followed through 2 to 3 years of Spanish courses; and administered standardized measures of Spanish achievement at the end of each year. Students were divided into high‐, average‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 82 publications
1
30
0
3
Order By: Relevance
“…Even at the end of third‐year Spanish, the average participant displayed a difference of over 3.0 SD s between Spanish word decoding and Spanish reading comprehension skills, for example, 50th percentile word decoding skill, <1st percentile reading comprehension skill. In another study with these participants, findings revealed little difference between the students’ Spanish reading comprehension and Spanish listening comprehension skills, even after 2–3 years of classroom instruction (Sparks, Patton, & Luebbers, ). That is, the students also achieved <1st percentile in Spanish listening comprehension, largely because they had acquired low levels of Spanish vocabulary (also <1st percentile).…”
Section: Simple View Of Reading Modelmentioning
confidence: 86%
See 1 more Smart Citation
“…Even at the end of third‐year Spanish, the average participant displayed a difference of over 3.0 SD s between Spanish word decoding and Spanish reading comprehension skills, for example, 50th percentile word decoding skill, <1st percentile reading comprehension skill. In another study with these participants, findings revealed little difference between the students’ Spanish reading comprehension and Spanish listening comprehension skills, even after 2–3 years of classroom instruction (Sparks, Patton, & Luebbers, ). That is, the students also achieved <1st percentile in Spanish listening comprehension, largely because they had acquired low levels of Spanish vocabulary (also <1st percentile).…”
Section: Simple View Of Reading Modelmentioning
confidence: 86%
“…Chapman and Tunmer () found that students’ self‐concept about their reading skill was moderately associated with their literacy skills in primary school. In a recent study with U.S. high school L2 learners Sparks et al () found that high‐achieving L2 learners displayed significantly more positive attitudes about L1 reading and engaged in significantly more L1 reading (print exposure) than average‐ and low‐achieving L2 learners.…”
Section: Component Model Of Readingmentioning
confidence: 99%
“…This means that students who are poorer at L1 decoding, and have reduced vocabulary range and lower spelling, writing, and language analysis skills, will demonstrate smaller achievement in FL classes. Students who have weaker L1 literacy skills will develop weaker FL literacy skills (Sparks, Patton, & Luebbers, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the apparent differences between the L1 and L2, it has frequently been emphasized that the development of second/foreign language skills and knowledge is closely connected to the skills already existing in one's mother tongue (Gottardo & Mueller, 2009;Sparks, Patton, Ganschow, & Humbach, 2009). In addition, research has confirmed the existence of interlingual interactions and transfer between L1 and L2 (Mihaljević Djigunović, 2006;Sparks, Patton, & Luebbers, 2019), and the interaction has also been found to be bi-directional (Brown & Gullberg, 2008;Pavlenko & Jarvis, 2002). In other words, multilinguals' competences may best be described if viewed holistically as a global system with dynamically interacting subsystems (Cook, 1992;Herdina & Jessner, 2002), where the two (or more) languages are constantly interacting, thus contributing to either positive or negative transfer between the languages (see Koda (2004) for an overview of language transfer research).…”
Section: The Transfer Of Skills Between L1 and L2mentioning
confidence: 99%